SYSTEM ANALYSIS OF THE IMPACT OF MATERIAL REPETITION, SET OUT EARLIER, ON THE ASSIMILATION OF THE NEW - Мокин, Борис; Войцеховская, Ольга (SWorldJournal, 2021)
The article presents the results of the research, in which on the basis of a system approach using the author’s mathematical models of the process of forgetting the knowledge obtained by the student at the lecture, it is mathematically substantiated that